2006
DOI: 10.1111/j.1399-0004.2006.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

CYLD mutations underlie Brooke–Spiegler, familial cylindromatosis, and multiple familial trichoepithelioma syndromes

Abstract: Brooke-Spiegler syndrome (BSS), familial cylindromatosis (FC), and multiple familial trichoepithelioma (MFT), originally described as distinct inherited disorders, are characterized by a variety of skin appendage neoplasms. Mutations in the CYLD gene are found in individuals with these syndromes. We describe a single family with affected members exhibiting either the FC or the MFT phenotypes associated with a mutation in the CYLD gene. These findings support the notion that BSS, FC, and MFT represent phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 33 publications
4
75
0
Order By: Relevance
“…CYLD, located at 16q12.1, was first identified as the relevant tumor suppressor gene in cylindroma tumors, a form of hereditary skin tumor. 48 Mutation of CYLD has been detected in cylindroma cases, 49 and mutations have been noted in myeloma. 50 CYLD is known to function as a negative regulator of the NF-B pathway, [34][35][36] and recent studies suggest that CYLD acts via the noncanonical NF-B pathway.…”
Section: Wwoxmentioning
confidence: 99%
“…CYLD, located at 16q12.1, was first identified as the relevant tumor suppressor gene in cylindroma tumors, a form of hereditary skin tumor. 48 Mutation of CYLD has been detected in cylindroma cases, 49 and mutations have been noted in myeloma. 50 CYLD is known to function as a negative regulator of the NF-B pathway, [34][35][36] and recent studies suggest that CYLD acts via the noncanonical NF-B pathway.…”
Section: Wwoxmentioning
confidence: 99%
“…An abnormality in this gene may result in one of three syndromes Brooke-Spiegler syndrome, familial cylindromatosis, and multiple familial trichoepithelioma. 1 We can find about thirteen reported cases in literature, and there is two reported trichoepithelioma of the thigh. Our case is the 3rd cases reported trichoepithelioma of thigh to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The germline mutations were then detected in individuals with BSS (HU et al, 2003;Poblete Gutiérrez et al, 2002) and MFT (Salhi et al, 2004;Zhang et al, 2004;Zheng et al, 2004). Affected family members with the same germline mutation in CYLD showed FC, BSS or MFT phenotypes, indicating the absence of genotype-phenotype relationship (Fenske et al, 2000;Rajan et al, 2009;Young et al, 2006). The phenotypic diversity from mild type to severe turban tumor is present in the affected family members with CYLD cutaneous syndrome (Biggs et al, 1995;Oiso et al, 2004;Rajan et al, 2009;Young et al, 2006).…”
Section: Cyld Cutaneous Syndromementioning
confidence: 99%
“…Affected family members with the same germline mutation in CYLD showed FC, BSS or MFT phenotypes, indicating the absence of genotype-phenotype relationship (Fenske et al, 2000;Rajan et al, 2009;Young et al, 2006). The phenotypic diversity from mild type to severe turban tumor is present in the affected family members with CYLD cutaneous syndrome (Biggs et al, 1995;Oiso et al, 2004;Rajan et al, 2009;Young et al, 2006). Bowen et al suggested that FC, BSS, and MTF represent phenotypic variation of a single entity (Bowen et al, 2005).…”
Section: Cyld Cutaneous Syndromementioning
confidence: 99%